(untitled) (International journal of medical sciences, 2026)
One of the most common complications of cardiovascular diseases is the development of heart failure syndrome (HFS). In developed countries, heart failure is one of the main causes of disability and death among the working-age population (WHO, 2005). The most common causes of heart failure are: ischemic heart disease (50-70%), arterial hypertension (12-17%), alcohol abuse (7-9%), diabetes mellitus (10%), cardiomyopathy (3-4%). The results of numerous studies confirm the direct involvement of systemic and local inflammation in the initiation and development of atherosclerosis and its complications. In this regard, infectious diseases of the oral cavity are considered a risk factor for the development of cardiovascular diseases.